Notes on Two Rare Species of Brachyuran Crabs (Families Matutidae and Parthenopidae) From Indonesian Waters with New Distribution Records - Nisfa Hanim; Ali Suman; Duranta Diandria Kembaren; Dyah Perwitasari; Yusli Wardiatno; Achmad Farajallah (Tropical Life Sciences Research, 2023)
Several species of brachyuran crabs in Indonesian waters have not been reported since almost 100 years ago. This research reports a brachyuran crab that is rarely found and one new record in Indonesian waters. This study was conducted in the waters of southern Aru Island and the Malacca Strait using trawls during a cruise held by the Research Institute for Marine Fisheries, Ministry of Marine Affairs and Fisheries, Indonesia.. Our findings were Izanami reticulata, a new record (family Matutidae) from southern Aru Island, and Cryptopadia fornicata (family Parthenopidae) from the Malacca Strait. The two locations are close to where the species were found in previous studies: the Arafura Sea, which is adjacent to the Aru Islands, and the Malacca Strait, which is adjacent to Borneo. It is suspected that the presence of these two species in Indonesia is due to their distribution through sea currents during the pelagic larval stage. This article also provides the specific habitat for both species in Indonesia, which was previously unknown. In addition, this article contributes to strengthening Indonesia as a mega-biodiversity country with an initial compilation of a database of Brachyura in its waters.